A remarkable new synthemistid from New Caledonia (Odonata: Anisoptera: Synthemistidae s. str.). Taxonomic and phylogenetic note on New Caledonian Synthemistidae and erection of a new genus - Fleck, Günther (Zootaxa, 2024)
The new species, Calesynthemis jeanlegrandi sp. nov., dedicated to the late Jean Legrand, is described and illustrated based on a single pair of specimens from Mont Panié, New Caledonia. The male of this large species has unusual strongly sinuous and distally down curved white cerci 7 mm long and exhibits on abdominal segment 10 a remarkable clump of strong setae mimicking a dorsal horn. The female wingspan slightly exceeds 100 mm. In addition, on the basis of adult and larval characters, Neocaledosynthemis gen. nov. is erected to accommodate two other New Caledonian synthemistids, Synthemis fenella Campion (type species) and Synthemis ariadne Lieftinck. New Caledonian synthemistids are probably more closely related to Parasynthemis Carle than to Synthemis Selys Longchamps, both from Australia.